2013
DOI: 10.1073/pnas.1309171110
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a small molecule with activity against drug-resistant and persistent tuberculosis

Abstract: Significance The global problem of TB has worsened in recent years with the emergence of drug-resistant organisms, and new drugs are clearly needed. In a cell-based high-throughput screen, a small molecule, TCA1, was discovered that has activity against replicating and nonreplicating Mycobacterium tuberculosis . It is also efficacious in acute and chronic rodent models of TB alone or combined with frontline TB drugs. TCA1 functions by a unique mechanism, inhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
215
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 204 publications
(228 citation statements)
references
References 32 publications
9
215
0
1
Order By: Relevance
“…M. smegmatis was used to show that lysogenization by bxb1 disrupted a GroEL-1 gene involved in biofilm formation (86). A promising new drug targeting persisters has been identified from screening for compounds inhibiting biofilm formation in M. smegmatis (87). The useful transposon (IS1096) was identified from the genome of mc 2 155 (88) and used to generate valuable auxotrophic mutants of bacillus CalmetteGuérin (89) and the first diverse genetic libraries in M. tuberculosis (90).…”
Section: Discussionmentioning
confidence: 99%
“…M. smegmatis was used to show that lysogenization by bxb1 disrupted a GroEL-1 gene involved in biofilm formation (86). A promising new drug targeting persisters has been identified from screening for compounds inhibiting biofilm formation in M. smegmatis (87). The useful transposon (IS1096) was identified from the genome of mc 2 155 (88) and used to generate valuable auxotrophic mutants of bacillus CalmetteGuérin (89) and the first diverse genetic libraries in M. tuberculosis (90).…”
Section: Discussionmentioning
confidence: 99%
“…The cross-resistance to the PyrBTZs displayed by the NTB1 strain and the newly generated PyrBTZ01-resistant mutants, due to the Cys387Ser mutation, was unexpected, since Cys387 is required for the binding of covalent nitroaromatic inhibitors, including nitroBTZs, but not noncovalent inhibitors (18). The PyrBTZs with nonsubstituted pyrroles were not expected to form covalent adducts with Cys387.…”
Section: Pyrrole-btz Analogues Are Potent Antimycobacterial Agentsmentioning
confidence: 93%
“…Additionally, recent studies identified "non-nitroaromatic" hits that bind to the same pocket as BTZ043 without formation of the covalent semimercaptal adduct. 11 Therefore, synthesis and evaluation of the anti-TB activity of 3 was of interest and is reported herein.…”
Section: T Uberculosis (Tb) Is a Disease Mainly Caused Bymentioning
confidence: 99%